Prevalence of Enterococcus species in adults with periodontal health or with periodontitis: a systematic review - Laís Christina Pontes ESPÍNDOLA; Adriana Miranda de OLIVEIRA; Daniele MASTERSON; Lucianne Cople MAIA; Renata Martins do SOUTO (Sociedade Brasileira de Pesquisa Odontológica, 2023)
Abstract The aim of this study was to evaluate the prevalence of Enterococcus species in the mouth of adults with periodontal health and periodontitis. A systematic search was made in databases in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines. The search for articles was conducted in Medline/PubMed, Latin American and Caribbean Health Sciences Literature Database (LILACS), Cochrane Library, Scopus, Embase, Web of Science databases and in the System of Information on Grey Literature in Europe (SINGLE) and included articles published in English up to April 25th, 2021. Observational studies in humans with and without periodontitis were evaluated to identify the prevalence of Enterococcus species. Articles that met the inclusion criteria were analyzed and classified to determine the quality rating in good, fair, and poor. A new detailed checklist for quality assessment was developed based on the information required for applicable data extraction in reviews. The study design, sample size, demographic data, periodontal clinical parameters, microbial analysis method, biological sample, prevalence of Enterococcus spp., and correlations with periodontal clinical parameters were assessed. After screening and full-text reading, 8 articles met the inclusion criteria. All selected studies showed a significantly higher prevalence of Enterococcus spp. in patients with periodontitis compared with periodontally healthy patients. Thus, the present systematic review suggests that the prevalence of Enterococcus faecalis in the mouth of periodontitis individuals is higher than that of periodontally healthy individuals.